Case Study : Olmos Diversion Project for Transforming Peru - Sharma, Aaryan; Rehalia, Arvind (AMC Indian Journal of Civil Engineering, 2020)
This project consists of a dam and a tunnel. The main aim of this project was to transport water from Cajamarca region to the Lambayeque region near Olmos. This transported water would make irrigation possible on 1,07,000 acres of arid farmland. The west and east regions of Peru separated by Andes mountains which are 7,000 ft high suffer two different extreme conditions. The west suffers a year long annual drought whereas, the East is flooded for most of the year. The only way out is to somehow transport the water from the flooded region to the fertile but dry farmlands to the west comprising of Peru’s 70% population. The project engineers faced major problems while on a seismically active site with plenty of earthquakes, landslides, and mudslides. Let us see how Peru made it possible.